2018
DOI: 10.2478/jcbtp-2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Determinants of Systemic Banking Crises in Southeast European Countries

Abstract: The purpose of this paper is to determine potential indicators of systemic banking crises in five Southeast European countries. Although signal horizon in the literature usually implies a period of 12 months before and 12 months after a crisis outbreak, models in this paper imply a 24-month pre-crisis period. Probability of a banking crisis occurrence is calculated using logit regression. Results have shown that banking system indicators have higher impact on probability of systemic banking crisis occurrence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…for Croatia see Dumičić, 2016; Ahec Šonje, 1999 and 2002, for Montenegro see Asanović, 2017) as well as the paper related to 5 Southeast European countries (i.e. Montenegro, Serbia, Bosnia and Herzegovina, Macedonia, and Croatia, see Asanović, 2018).…”
Section: Finance-growth Nexus In Southeast European Countriesmentioning
confidence: 93%
“…for Croatia see Dumičić, 2016; Ahec Šonje, 1999 and 2002, for Montenegro see Asanović, 2017) as well as the paper related to 5 Southeast European countries (i.e. Montenegro, Serbia, Bosnia and Herzegovina, Macedonia, and Croatia, see Asanović, 2018).…”
Section: Finance-growth Nexus In Southeast European Countriesmentioning
confidence: 93%
“…The agents of stock markets are involved in researching the firms to disseminate information which in effect promotes better access to relevant information and capital allocation. Asanović (2018) found that businesses depending on each other find more benefits in countries with better developed financial markets, i.e. the resource allocation is better where the finance is strong.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Koju et al (2018) shown the effects of remittance, public debts and interest spreads on NPL of each specific bank within the Nepalese banking system. Asanović (2018) performed an analysis of the determinants of banking crisis in Southeast European Countries and the results of the study shown that the banking system indicators have higher impact on probability of systemic banking crisis occurrence compared to macroeconomic indicators.…”
Section: Most Of Previous Studies Analyzed the Relation Between Macroeconomic Factors And Credit Risk Indicators Such As Non-performing Lmentioning
confidence: 99%